Da segurança privada e serviços de autoproteção - Silva, Jennifer (2022)
In the present research work with a view to obtaining a Master's Degree, through the completion of the Master's Degree in Law and Safety, a reconciliation was sought between one of the areas of study covered by the teaching part of the Master's Degree and the professional activity performed by the Master's candidate. In this regard, the area of Private Security was related to Food Distribution Companies in Portugal, with a view to understanding the role of Private Security in this sector of the economy and also of society. Private Security is an increasingly current issue, not only because it is part of a sensitive area for any Rule of Law, which makes it possible to guarantee its survival - Security - but also because of the space it has been gaining in society and in the economy. The development of the Private Security area has also been visible in the legislative evolution in the last decades, due to the constant need to adapt the legal regime to what reality demands. Food distribution is also a strategic sector for the State, by ensuring the suppression of basic needs of the population, enabling better distribution and access to a wide variety of food products, in addition to the jobs it creates annually and the generation of wealth, which represents a significant percentage in the Portuguese Gross Domestic Product (GDP). In the logical construction of the dissertation, it was decided to approach the concepts of Security in general, Private Security and Self-Protection Services in particular; a brief historical-legal analysis of the Private Security Activity Regime (REASP) was carried out; the concept of distribution was addressed, as well as the historical evolution of retail trade and modern distribution and a brief case study of a Security Department was dealt with, and finally, surveys of two Security Directors were analysed. The main conclusion drawn is that the vision that companies have of the Security Department should be to consider these departments as an investment centre rather than a cost centre, changing in this light the essential part of their contribution to successfully overcoming the challenges faced by the Food Distribution Companies on a daily basis.